Seismic assessment and loss estimation of existing school buildings in Italy. (1st August 2018) - O'Reilly, Gerard J.; Perrone, Daniele; Fox, Matthew; Monteiro, Ricardo; Filiatrault, Andre
Highlights: Seismic assessment of Italian schools to show different facets to practitioners. Three building typologies and two site locations are considered. Detailed assessment conducted using in-situ surveys and inventories. Loss and collapse assessment performed for each scenario. Critical discussion of existing approaches and frameworks provided. Abstract: Extensive damage to school buildings has been observed during past earthquakes in Italy and there is a need to better understand their potential vulnerability. As part of a national project to assess seismic risk in Italian schools, a database was compiled in terms of characteristics such as school location and construction typology. This paper examines a number of these buildings considered to be a representative sample of the Italian school building population. To quantify their seismic vulnerability, the induced damage with respect to increased shaking intensity need to be quantified. This characterisation of the building vulnerability, in combination with the seismic hazard, allows more informed, risk-based decisions to be made using performance metrics such as expected annual loss (EAL). This article outlines a case study application quantifying the EAL and collapse safety for three school buildings representative of the Italian school building stock. Detailed numerical models were developed using information collected during in-situ inspections in order to accurately represent the dynamic response of the school structures. To estimate economic losses, a structural and non-structural element inventory was compiled using in-situ survey information. This case study application is conducted in a systematic fashion to clearly illustrate the various details required to implement more advanced seismic assessment studies. Finally, a comparison is made with the seismic classification guidelines recently introduced in Italy to provide further insight into how these can be used to identify existing buildings vulnerable to excessive damage and potential collapse during earthquakes.